Development of an electronic student worksheet based on REPIDS to improve students' science process skills and critical thinking - Mualidiyah, Ulyana; Suratno, Suratno; Nuriman, Nuriman (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2025)
Responding to the increasing demand for 21st-century skills, such as critical thinking and science processes, in solving environmental issues. The study aims to develop and evaluate REPIDS-based electronic student worksheets to improve students' science process skills and critical thinking in the topic of environmental pollution among vocational high school students. This study uses the Research and Development (R&D) method through the 4D model, which includes define, design, develop, and disseminate. This study was conducted up to the development stage and included part of the initial dissemination stage to assess the effectiveness of the product. The instruments used included expert validation sheets, classroom observation forms, and pre-test and post-test questions. Participants were tenth-grade vocational students selected through purposive sampling. Data were analyzed using percentage scores for validity and practicality, and normalized gain scores (N-gain) to measure effectiveness. The results of the study indicate that the developed REPIDS-based electronic student worksheet meets the criteria of validity (content aspect of 92%, language aspect of 85%, and design aspect of 90%), practicality (85%), and effectiveness (N-gain of 0.65, medium criteria) in improving science process skills and critical thinking. REPIDS-based electronic student worksheet is recommended for wider use in science education to support meaningful and skill-oriented learning.